2020
DOI: 10.3389/fmicb.2020.583588
|View full text |Cite
|
Sign up to set email alerts
|

Truncation or Deglycosylation of the Neuraminidase Stalk Enhances the Pathogenicity of the H5N1 Subtype Avian Influenza Virus in Mallard Ducks

Abstract: H5N1 subtype avian influenza virus (AIV) with a deletion of 20 amino acids at residues 49-68 in the stalk region of neuraminidase (NA) became a major epidemic virus. To determine the effect of truncation or deglycosylation of the NA stalk on virulence, we used site-directed mutagenesis to insert 20 amino acids in the short-stalk virus A/mallard/Huadong/S/2005 (SY) to recover the long-stalk virus (rSNA+). A series of short-stalk or deglycosylated-stalk viruses were also constructed basing on the longstalk virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Three mutations in NA (N46K, N84S and T295M) deserve special mentioning because these mutations remove predicted N-linked glycosylation sites and thus are assumed to diminish glycosylation in the NA stem region. There are experimental studies showing that the abrogation of the NA glycosylation enhances the virulence, increases pathology in birds and mice ( Chen et al, 2020 ; Park et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three mutations in NA (N46K, N84S and T295M) deserve special mentioning because these mutations remove predicted N-linked glycosylation sites and thus are assumed to diminish glycosylation in the NA stem region. There are experimental studies showing that the abrogation of the NA glycosylation enhances the virulence, increases pathology in birds and mice ( Chen et al, 2020 ; Park et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those results strongly suggest that the higher stability and EA resistance of the H5N1 subtype might depend on NA, a spike protein. Although several studies have focused on the relationship between the NA segment and virulence ( 42 , 43 ), to the best of our knowledge, no study has focused on the relationship between the NA segment and stability. Future studies focusing on the NA segment are expected to elucidate factors that determine the stability and help identify subtypes with high stability and a high risk for contact transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions in the NA stalk have been associated with poultry adaptation [ 14 , 15 , 16 , 17 , 64 ], outbreaks in the field [ 34 ], and experimental virus passage in gallinaceous birds [ 37 , 38 ]. Other studies showed that influenza viruses with different NA stalk lengths have different in vitro growth characteristics and plaque size [ 39 , 65 , 66 ] and differences in pathogenesis in ducks and chickens [ 39 , 63 ]. A study demonstrated that an amino acid deletion in the NA stalk can remove potential glycosylation sites, which may interfere in the protein’s function due to possible changes in the structure and consequently affect the immune response [ 67 ].…”
Section: Discussionmentioning
confidence: 99%